Discovery and clinical translation of novel glaucoma biomarkers. (January 2021) - Beykin, Gala; Norcia, Anthony M.; Srinivasan, Vivek J.; Dubra, Alfredo; Goldberg, Jeffrey L.
Abstract: Glaucoma and other optic neuropathies are characterized by progressive dysfunction and loss of retinal ganglion cells and their axons. Given the high prevalence of glaucoma-related blindness and the availability of treatment options, improving the diagnosis and precise monitoring of progression in these conditions is paramount. Here we review recent progress in the development of novel biomarkers for glaucoma in the context of disease pathophysiology and we propose future steps for the field, including integration of exploratory biomarker outcomes into prospective therapeutic trials. We anticipate that, when validated, some of the novel glaucoma biomarkers discussed here will prove useful for clinical diagnosis and prediction of progression, as well as monitoring of clinical responses to standard and investigational therapies.